Effects of a New Kappa Agonist (Fluorophenyl Derivative of Imidazo[1,2-а]benzimidazole) on the Rat Genome - O. V. Verle; A. G. Sirekanyan; N. V. Eliseeva; Yu. V. Lifanova; A. A. Spasov; O. V. Ostrovsky (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Selective kappa-opioid receptor (KOR) agonists are considered a promising group of substances for developing opioid analgesics characterised with an original mechanism of action without the risk of respiratory depression and drug addiction. Previous studies identified a fluorophenyl derivative of imidazo[1,2-a]benzimidazole (RU-1205) with a KOR-based mechanism of analgesic action established in in vitro and in vivo experiments.The aim of the study was to assess the effect of 9-(2-morpholinoethyl)-2-(4-fluorophenyl)imidazo[1,2-a]benzimidazole dihydrochloride on the level of DNA damage in rats after a single subcutaneous injection.Materials and methods. The study was conducted in adult white outbred laboratory rats of both sexes. DNA damage was estimated using the comet assay. The study involved a single subcutaneous injection of an aqueous solution of RU-1205 in three doses: 1, 10, and 100 mg/kg. The authors used intraperitoneal methyl methanesulfonate (40 mg per kg of animal body weight) as a positive control and 0.9% NaCl  (100 μL per 100 g of animal body weight) as a negative control.Results. A single subcutaneous injection of RU-1205 to rats did not produce a significant dose-dependent increase in % tail DNA when compared with the state of   the corresponding organ/tissue cell genome in negative control animals after normal saline administration at the same time points. In the negative control groups, % tail DNA in cells of various organs/tissues ranged from 1.83% to 3.82% (median values [25–75%]). On the contrary, the administration of 40 mg/kg of genotoxic methyl methanesulfonate led to an increase in damaged DNA in all studied organs and tissues when compared with negative control animals.Conclusions. The study of 9-(2-morpholinoethyl)-2-(4-fluorophenyl)imidazo[1,2-a] benzimidazole dihydrochloride genotoxicity demonstrated that a single subcutaneous injection of 1, 10, or 100 mg/kg of RU-1205 to rats did not damage the cell genome of the studied organs.